2016
DOI: 10.1039/c5ra27761b
|View full text |Cite
|
Sign up to set email alerts
|

Effects on emissions of a diesel engine with premixed HHO

Abstract: Most parts of China suffer often from haze pollution, which has a huge impact on human health. Road traffic has made the largest contribution to the haze. Of all the kinds of vehicular systems, the diesel engine produces the most PM; therefore, to reduce haze pollution, it is necessary research methods to reduce the PM produced by diesel engines. HHO (Brown's gas, Rhode's gas and HRG) is formed from H 2 (60.79%) and O 2 (30.39%) as well as a small amount of water vapour and active substances, such as oxygen ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…15 Variation of HC emission with respect to brake power and fuels During combustion, HHO generated more OH free radicals which enhance the reaction with the C-H chain due to its strong oxidizing properties and continuously oxidized unburned HC after the main combustion period. Thus, HC emission is reduced (35). Higher diffusion speed of hydrogen makes the fuel mixture gain better homogeneity, and therefore enhances the engine thermal efficiency and reduces the unburnt HC emissions (31).…”
Section: Hc Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Variation of HC emission with respect to brake power and fuels During combustion, HHO generated more OH free radicals which enhance the reaction with the C-H chain due to its strong oxidizing properties and continuously oxidized unburned HC after the main combustion period. Thus, HC emission is reduced (35). Higher diffusion speed of hydrogen makes the fuel mixture gain better homogeneity, and therefore enhances the engine thermal efficiency and reduces the unburnt HC emissions (31).…”
Section: Hc Emissionmentioning
confidence: 99%
“…Liu et al [23] reported that HHO accelerates the oxidation process and CO, HC and smoke emission declined gradually when load increased, but the drop of NO was comparatively smaller. Addition of 20% hydrogen leads poor diesel-air quantity which is not sufficient to develop healthy flame to ignite the hydrogen-diesel-air mixture.…”
Section: Introductionmentioning
confidence: 99%